Fabricating and constructing one’s own identity: Bai Yao’s revisit of Nanyang - Lim, Choon Bee (Center for Chinese Studies, 2018)
Bai Yao arrived in Malaya immediately after the country gained independence. As one of the leading figures of the Students Weekly and Chao Foon magazines, his works had prompted the first wave of modernism in the history of Mahua literature. He disappeared from the local literary arena after emigrating to the United States in the 1980s, but re-emerged in Chao Foon and Nanyang Literature magazines at the end of the 20th century. The publication of his complete works Lü yun qi yu lü cao 縷雲起於綠草 and his unfinished autobiographical novel Lü yun qian shu 縷雲前書 in Malaysia may carry particular significance. This article examines his “Nanyang” experiences during the two different periods and discusses the different dimensions of the construction of his identity.